Efficient one-pot fructose to DFF conversion using sulfonated magnetically separable MOF-derived Fe3O4 (111) catalysts. Issue 3 (28th September 2016) - Fang, Ruiqi; Luque, Rafael; Li, Yingwei
Abstract : A highly efficient and recyclable non-noble heterogeneous catalyst is developed for one-pot conversion of fructose into 2, 5-diformylfuran with extremely high yields (>99%). Abstract : Aerobic oxidation of carbohydrate-derived 5-hydroxymethylfurfural (HMF) into high added-value 2, 5-diformylfuran (DFF) has attracted much attention in recent years. However, the direct synthesis of DFF from cheap and abundant carbohydrates via HMF as an intermediate through a one-pot process is highly desirable but challenging. In this work, we have developed a highly efficient and recyclable non-noble heterogeneous catalyst for one-pot conversion of fructose into DFF with extremely high yields (>99%). The catalyst was prepared by a simple pyrolysis method using Fe-based metal–organic frameworks (MOF) as a template and sulfur powder as a dopant. The pyrolysis of the MOF template under interactions of Ostwald ripening and Kirkendall effects led to the formation of uniform octahedral Fe3 O4 nanoparticles with exposed (111) crystal facets highly dispersed on sulfur doped carbon. The superior selectivity to DFF over the designed Fe-based catalyst is related to the low adsorption energy of DFF on the support as well as the existence of non-oxidized sulfur that makes the catalytic system less oxidative.